PERLAWANAN PEREMPUAN DALAM KARYA DUA KOREOGRAFER: HARTATI DAN SUSASRITA LORAVIANTI - Roza Muliati (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2011)
Hartati and Susasrita Loravianti are both Minangkabau female leading choreographers nowadays, who have been known for their consistency, quality, and their sensibility toward the issue of gender.  This article aims to reveal the ideology presented in the works of both choreographers and to show the critical dimension of both choreographers toward the factual problem of women today which is remain opposing traditional rules. This article is a textual study of women opponent which is reflected in the works of both choreographers, namely: Hari Ini and Ritus Diri  by Hartati; and Perempuan dalam Kaba, and Meja, Kursi, dan Segelas Jus yang Tumpah by Susasrita Loravianti.